Dynamic of Particulate Organic Matter and Phytoplankton in Akkeshi-ko Estuary - Ma’ruf Kasim (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2010)
This research was to clarify the dynamic of particulate organic matter (POM) and species composition of phytoplankton in an estuarine. C/N ratio was measured in a C-N Analyzer and phytoplankton was identifying under electron microscope. The seasonal uctuation of POC and PON concentration was generally similar in all stations. POC and PON concentration were generally higher in inert part of estuary during spring and summer and its concentrations seem high at outside part during autumn. From total 128 species of diatoms identied in the Akkeshi-ko estuary, 103 and 102 species of phytoplankton occurred on the upper layer of sediments and in water column, respectively. On the upper layer  sediments, there were 12 species of benthic diatoms and 2 species of pelagic diatoms were most common and dominantly occurred in all stations. In water column, 12 species of benthic diatoms and 3 species of pelagic diatoms were most common and predominantly occurred in all stations. The main reason of this condition is the concentration of POM and phytoplankton was increase during spring and summer cause of high input nutrient from outside of estuarine.Key words :  particulate organic matter, phytoplankton, benthic diatom, pelagic diatom. Penelitian ini dilakukan untuk mendapatkan gambaran yang jelas mengenai dinamika dari bahan organik terlarut dan komposisi jenis dari fitoplankton pada perairan estuari Hokkaido.  C/N ratio diukur dengan menggunakan C/N analyzer dan identifikasi fitoplankton dilakukan di bawah mikroskop elektron. Fluktuasi musiman dari konsentasi PON dan POC dalam perairan relatif sama di seluruh stasiun pengamatan. Konsentrasi POC dan PON relatif  lebih tinggi pada bagian dalam Akkeshi estuary selama musim semi dan musim panas dan konsentasi tersebut terlihat lebih tinggi di luar lokasi estuari selama musim gugur. Dari total 128 jenis yang diidentifikasi di lokasi penelitian, 103 spesies fitoplankton ditemukan pada permukaan sedimen dan 102 diantaranya ditemukan mengapung di perairan.  Pada permukaan sedimen ditemukan 12 spesies dari diatom bentik dan 2 spesies dari diatom pelagik dan mendominasi lokasi penelitian. Pada kolom air ditemukan 12 spesies dari diatom bentik dan 3 spesies dari diatom pelajik  ditemukan dominan dan mendominasi lokasi penelitian. Hal ini disebabkan oleh terjadinya peningkatan bahan organik terlarut dan fitoplankton selama musim semi dan musim panas yang disebabkan oleh peningkatan kandungan nutrien yang berasal dari luar perairan estuari. Kata kunci:  Bahan organic terlarut, fitoplankton, bentik diatom, pelagik diatom